PERENCANAAN PENGEMBANGAN MADRASAH DI MAS TERPADU GUGUAK RANDAH - Efnaliza; Nadia Gustina; Asmendri; Milya Sari (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
The objective of this research is to understand the development planning of the Madrasah at MAS Terpadu Guguak Randah, Kecamatan IV Koto, Kabupaten Agam. This study was conducted at the Madrasah and used a qualitative method. The results show that the development planning at MAS Terpadu Guguak Randah aims to achieve a superior status, beginning with improvements in the learning process. Furthermore, improvements are needed in the new student admission system (input), ensuring that teachers have adequate professionalism and competencies. Additionally, sufficient supporting facilities and infrastructure must be available, along with management that has a global and progressive vision, as well as long-term thinking. Extracurricular activities are also considered important as a means to appreciate individual potential, accompanied by an adequate budget to meet these needs.